Study of the performance and emissions of diesel engines operating by blends of Jatropha biodiesel, diesel and pentanol. (2023) - Ponnappan Venkatesan, Sorakka; Srihariharan, P.; Rohith, B.; Purusothaman, M.; Venkatesh, S.
Abstract: Nowadays fossil fuels have become very expensive and polluting it is therefore necessary to look for an alternative fuel which is biodiesel which had recently become one of the promising fuels. The present aim of this work is to experiment with a compression ignition engine using jatropha blended with diesel and pentanol as an additive in different ratios. The present experiment is carried out in a constant-speed, direct-injection, water-cooled engine at different loads with eight different blends. The blends are prepared as follows: Jatropha25Diesel75Pentanol10, J50D50P10, J25D75P10, J100P10, J25D75P15, J50D50P15, J75D25P15, J100P15 and are tested in a diesel engine. The experimental results show that there is a 1.28 % increase in engine efficiency, a 10 % increase in nitric oxide emissions, a 22.35 % decrease in smoke opacity and a 22.58 % decrease in hydrocarbon emissions compared to base fuel.